The handbook of rational choice social research / edited by Rafael Wittek, Tom A.B. Snijders, Victor Nee. - Wittek, Rafael, 1965-; Snijders, T. A. B.; Nee, Victor, 1945- (Stanford Social Sciences, an imprint of Stanford University Press, 2013)
The Handbook of Rational Choice Social Research offers the first comprehensive overview of how the rational choice paradigm can inform empirical research within the social sciences. This landmark collection highlights successful empirical applications across a broad array of disciplines, including sociology, political science, economics, history, and psychology. Taking on issues ranging from financial markets and terrorism to immigration, race relations, and emotions, and a huge variety of other phenomena, rational choice proves a useful tool for theory- driven social research.